Prevalence of celiac disease-specific antibodies and their association with clinical status and environmental factors - de Diego, Gabriel Alejandro; Cerny, Natacha; Tolosa, Gabriel; Lulic, Maximiliano; Fusco, Mariel; Belforte, Fiorella Sabrina; Martínez Ruiz, Brian; Tamborenea, María Inés; Cánepa, Ana; Cimarelli, Margarita; Ghiglieri, Rosana; Díaz, Eugenia; et al. (Heliyon, 2024)
Celiac disease (CeD) affects 1–2% of the world's population. The aim of this study was to relate the incidence of CeD-related serological markers to symptoms, pathologies, and environmental exposure to wheat flour, given the number of flour mills present in the region. Serum samples were collected from 537 inhabitants from a rural city. Levels of anti-transglutaminase (a-tTg), anti-gliadin, anti-DGP antibodies and total IgA levels were measured. Volunteers completed a questionnaire covering environmental factors, demographics, pregnancies, other diseases, symptoms, and CeD diagnosis. Geo-referencing of volunteers' homes and mills in the city was performed, and correlations between the different parameters assessed were analysed. A CeD incidence of 1.76 % was found. However, a-tTg and a-gliadin levels were elevated in the population without CeD diagnosis (9.6 % and 30.1 %). Subjects with CD diagnosis showed diarrhoea and colic pain. Women with CeD had fewer pregnancies. Positive a-tTg and number of CeD-associated symptoms appear to correlate with proximity to flour mills. A high prevalence of CeD-related specific antibody positivity in a rural population was found, possibly due to environmental factors related to flour mills. Further research is needed to better understand CeD's pathogenesis and its health implications. •A higher prevalence of CeD-specific antibodies was found in a rural population.•CeD diagnosis correlate with fewer pregnancies.•Antibodies a-tTg and CeD-associated symptoms correlate with proximity to flour mills.•CD may be activated by ingesting wheat gluten or by exposure to wheat flour in the air.